POPULATION DYNAMICS OF THREE SPECIES OF CYPRINIDS IN KEDUNGOMBO RESERVOIR, CENTRAL JAVA - Endi Setiadi Kartamihardja (Research Center for Fisheries, 1995)
A study the growth, mortality, exploitation rate and recruitment of three species ofcyprinids (Puntius gonionotus, P. bramoides and Mystacohucts marginatus) was carried out in Kedungombo reservoir, Central Java.